(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Ground beetle species assemblages in seven different crops (meadow, irrigated meadow, sunflower, alfalfa, herbaceous waste land and two maize) have been analysed during 1994. Meadows are the most rich and steady areas, while maize and sunflower the less, both according to the indices of diversity, and according to the ratio winged/unwinged specimens. One of the two maize crops, farmed as a meadow the previous year, shows a species assemblage similar to those of the meadows, although disturbed. Meadows and alfalfa are the areas where more species and more specimens live, while the herbaceous waste land, although showing more natural numerica! trends, has no meaning as a source of ground beetles towards cultivated areas.